6+7(x-1)=11-9(x-4)

Simple and best practice solution for 6+7(x-1)=11-9(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+7(x-1)=11-9(x-4) equation:


Simplifying
6 + 7(x + -1) = 11 + -9(x + -4)

Reorder the terms:
6 + 7(-1 + x) = 11 + -9(x + -4)
6 + (-1 * 7 + x * 7) = 11 + -9(x + -4)
6 + (-7 + 7x) = 11 + -9(x + -4)

Combine like terms: 6 + -7 = -1
-1 + 7x = 11 + -9(x + -4)

Reorder the terms:
-1 + 7x = 11 + -9(-4 + x)
-1 + 7x = 11 + (-4 * -9 + x * -9)
-1 + 7x = 11 + (36 + -9x)

Combine like terms: 11 + 36 = 47
-1 + 7x = 47 + -9x

Solving
-1 + 7x = 47 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-1 + 7x + 9x = 47 + -9x + 9x

Combine like terms: 7x + 9x = 16x
-1 + 16x = 47 + -9x + 9x

Combine like terms: -9x + 9x = 0
-1 + 16x = 47 + 0
-1 + 16x = 47

Add '1' to each side of the equation.
-1 + 1 + 16x = 47 + 1

Combine like terms: -1 + 1 = 0
0 + 16x = 47 + 1
16x = 47 + 1

Combine like terms: 47 + 1 = 48
16x = 48

Divide each side by '16'.
x = 3

Simplifying
x = 3

See similar equations:

| 11y=y^3 | | n^2+3n-88= | | 3x^2=-3-4x | | 1/19x380 | | 2a(a-1)-2a^2= | | 108=2u^2+12 | | 75=y^2+3 | | -8x+6=9-9x | | -5(x+3)+84=4x-9(x-5) | | Factorx^2-10x= | | r/q-a/=1 | | 9x-12x-7=0 | | a^4b^5-a^5b^4=0 | | 35x5y2-75x3y4/-15x3y2 | | 2t-7=14-t | | 6(2x-4)-4(x+2)-18x= | | x/2-y/2=-1 | | 5(2x-5)-4(x+3)-20x= | | 2+6(X-5)=11-3(X-9) | | 12=2X+9 | | 17-9/2x=2 | | ln*x=ln*(x-5)+ln*6 | | 150/5-7x=3/2 | | 32-16x=64 | | 4x-5/2y=-15 | | 3x-y/y-3x | | -4x+4(-2x-4)=-22-6x | | n^2+7=8 | | -3*3*(-3)^2-(-5)/3*3*5 | | ((p^-5)^2)/(8p^6 | | v^2-16v-20=0 | | 112=r*28 |

Equations solver categories